Awareness, Knowledge, and Perceptions of Barotrauma and Barotrauma Mitigation: A Survey of Florida Anglers - Charles Adams; Joy Hazell; Lisa Krimsky; Bryan Fluech; Betty Staugler; John Stevely; Robert Bolta (EDIS, 2017)
Saltwater recreational fishing is an important economic engine for Florida’s coastal communities. The annual economic impact to the Florida economy of saltwater recreational fishing, which sustains 110,000 jobs, is estimated to be $13 billion. Given the popularity and economic importance of reef fish, careful management of these fish stocks is imperative for the sustainability of the reef-fish resource. Barotrauma, a phenomenon that causes problems for deep-water fish caught and brought to the surface, is recognized by fishery managers as a key cause of death in “catch-and-release” reef fish. This 5-page fact sheet describes a recent survey of Florida saltwater anglers and sheds light on incentives for and constraints against the use of barotrauma mitigation devices. Written by Charles Adams, Joy Hazell, Lisa Krimsky, Bryan Fluech, Betty Staugler, John Stevely, and Robert Botta, and published by Food and Resource Economics Department, March 2017.